MAFG-AS1 is a prognostic biomarker and facilitates prostate cancer progression - Li, Peizhang; Shi, Yuanping; Guo, Miaomiao; Xu, Huan; Zhan, Ming; Wang, Zhong; Chen, Yanbo (Frontiers in Oncology, 2022)
Long Noncoding RNAs (LncRNAs) have recently been identified as key regulator in tumor progression. The LncRNA MAFG-AS1 has been reported to facilitate the progression of multiple cancers, however, its role in prostate cancer is still unknown. Here, we reported that MAFG-AS1 was upregulated in prostate cancer. Importantly, high expression of MAFG-AS1 indicated advanced stage prostate cancer. Univariate and Multivariate Cox regression analyses showed that high MAFG-AS1 expression was independently correlated with poor progression-free interval (PFI). According to the result of The Cancer Genome Atlas (TCGA) database and tissue microarray, high MAFG-AS1 expression indicated a poor prognosis in prostate cancer patients. In addition, gene functional enrichment analysis revealed that MAFG-AS1 may be involved in ribosome biogenesis, ribonucleoprotein complex subunit organization, ribonucleoprotein complex assembly, rRNA metabolic process, structural constituent of ribosome, and ribonucleoprotein complex binding. Furthermore, MAFG-AS1 knockdown by siRNA markedly impaired prostate cancer cell proliferation, migration, and invasion.